Woman with Giant Lesion in the Trunk - Hanae BOUZIDI; Salim Galouj (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
The congenital melanocytic nevus is a type of melanocytic nevus found in infants at birth. This type of birthmark occurs in an estimated 1% of infants worldwide. It may be divided into the Small, mediumsize congenital nevocytic nevus and giant congenital melanocytic nevus also known as "Bathing trunk nevus,". We report a case in a 42-year-old woman.